Oxidized alkaline biochar and phosphate solubilizing bacteria mixture enhances direct seeded maize yield in an acid soil - Hachib Mohammad Tusar; Md. Kamal Uddin; Shamim Mia; Susilawati Kasim; Samsuri Bin Abd. Wahid; Tomoyuki Makino; Zakaria Solaiman (Universitas Sebelas Maret, 2025)
Maize is an important cereal in many developed and developing countries of the world. One of the primary challenges for maize cultivation is soil acidity. Acidic soil is a major constrain in achieving food security requiring sustainable solutions. Biochar, a pyrogenic carbon-rich material, carries reactive surfaces (i.e., high surface area and variable surface charges). Therefore, it facilitates nutrient retention in soil and gradual release to plants, thereby supporting crop growth. However, the combine effects of functionalized biochar with microbes on phosphorus (P) bioavailability and plant performance remain unclear. This study investigates the application of different oxidized biochars (i.e.,fresh rice husk biochar (RHB), pH adjusted oxidized RHB and control) and phosphate solubilizing bacteria (i.e., Pseudomonas aeruginosa, and control) on soil properties including phosphorus dynamics and the performance of maize grown in an acid soil. Biochar was oxidized using 10% hydrogen peroxide while the pH was adjusted to 8.5. Maize was grown in pots having 20 kg of soil or soil-biochar mixture. Overall, biochar and microbes treatments increased soil phosphorus bioavailability and maize yield with a greater effects in the oxidized biochar giving a significant biochar × microbes interactions. Specifically, oxidized biochar when applied with Pseudomonas aeruginosa increased P availability by 380 % which then contributed to yield increment (291%). We also observed a significant reduction in available aluminum (Al) concentration (40% ) compare to the control. These improvement in yield might have occurred due to an increase soil pH, P bioavailability (r2= 0.74), and a reduction in Al toxicity (r2= 0.36).Findings of this study could have significant implications for crop production in acidic soil.